(untitled) (Research, Society and Development, 2023)
This research aimed to present and analyze a didactic experiment using the three-dimensional version of GeoGebra, aiming at teaching and learning spatial geometry, in particular, the study of Clepsydra using Cavalieri’s Principle, in a practical and dynamic application. The research had a qualitative character, with field research, carried out in a class of the 3rd year of high school at the Fluminense Federal Institute – IFF, located in the city of Campos dos Goytacazes, in the State of Rio de Janeiro. Didactic experimentation was based on the action-research methodology and the activities were designed with the objective of developing skills necessary for students, exploring their use in a perspective of improvement and overcoming the learning difficulties found in the studies of three-dimensional geometries. With interactive animations, the involvement between technology and mathematical learning was provided. It can be concluded that the contents exposed in a dynamic perspective, significantly facilitated the teaching and learning process in spatial geometry.